1994
DOI: 10.1172/jci117244
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid cachexia: cytokine-driven hypermetabolism accompanying reduced body cell mass in chronic inflammation.

Abstract: The cytokines IL-10 and TNF-a cause cachexia and hypermetabolism in animal models, but their role in human inflammation remains controversial. The relationship between in vitro cytokine production and metabolism was examined in 23 adults with RA and 23 healthy control subjects matched on age, sex, race, and weight. Body composition was measured by multicompartmental analysis of body cell mass, water, fat, and bone mass. Resting energy expenditure (REE) was measured by indirect calorimetry. Cytokine production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
352
4
15

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 538 publications
(394 citation statements)
references
References 50 publications
23
352
4
15
Order By: Relevance
“…Leucine flux at baseline-a measure of whole-body protein turnover, and in the fasting state, equals protein breakdown-was directly associated with TNFa production (Figure 3). TNFa production was increased in patients with RA compared with controls in this study and in our previous studies (2,3). These findings suggest that elevated TNFa levels lead to increased protein breakdown in patients with RA.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Leucine flux at baseline-a measure of whole-body protein turnover, and in the fasting state, equals protein breakdown-was directly associated with TNFa production (Figure 3). TNFa production was increased in patients with RA compared with controls in this study and in our previous studies (2,3). These findings suggest that elevated TNFa levels lead to increased protein breakdown in patients with RA.…”
Section: Discussionsupporting
confidence: 83%
“…Previous work from our laboratory has shown that body cell mass and physical activity are significantly reduced, and resting energy expenditure (REE) significantly increased, in patients with RA compared with healthy age-, sex-, race-, and weight-matched controls (1)(2)(3). This hypermetabolism of RA (defined as an increase in REE by >lo% above predicted levels) was directly associated with the production of tumor necrosis factor a (TNFa) and interleukin-lp (IL-1p) by peripheral blood mononuclear cells (PBMC) from these patients, which was approximately 2-fold higher than that in the control subjects.…”
mentioning
confidence: 99%
“…Furthermore, when estimating the TEE by means of the AR, the PAL-value obtained was multiplied by the BMR estimated using the equations by the Department of Health (1991), which are standard equations not specifically developed for individuals with RA. In a study by Roubenoff et al (1994), the resting energy expenditure (REE), after adjustment for body cell mass, was found to be higher in RA patients compared to healthy controls. Furthermore, in the group of RA patients the REE increased with the cytokine production.…”
Section: Validity Of the Reported Energy Expenditurementioning
confidence: 99%
“…Such a situation has been clearly demonstrated for acute illness and for chronic in¯ammatory conditions such as rheumatoid arthritis and HIV infection (Roubenoff et al, 1994). There is moderately strong evidence that aging is associated with immune senescence that includes loosening of the tolerance which allows a healthy immune system to correctly identify`self ' from`non-self ' antigens and avoid targeting self antigens.…”
Section: Humoral Factorsmentioning
confidence: 99%